ІНДЕТТІ КЕРАТОКОНЬЮНКТИВИТПЕН АУЫРАТЫН ІРІ ҚАРА МАЛ КӨЗІНІҢ ЖЕРГІЛІКТІ ИММУНИТЕТ КӨРСЕТКІШТЕРІНЕ ФИТОПРЕПАРАТТАРДЫҢ САЛЫСТЫРМАЛЫ ӘСЕРЛЕРІ - К. Боранбаева; Н. Заманбеков; А. Бакбаева; Ш. Туржигитова; М. Батырханов; Д. Хусаинов; С. Нусупова; Р. Саттарова; А. Мыржиева; А. Джангабулова (Animal Health and Biosafety, 2026)
The main purpose of the research conducted in this article is the development of phytopreparations (phytoointments) from local plant raw materials and a comparative study of their effect on the local immunity of cattle infected with infectious keratoconjunctivitis. To achieve this goal, eye ointments were made from chamomile flowers (fl. Chamomilla L.), aloe branches (Aloe ferax L.) and mature sea buckthorn fruits (Hippophae rhamnoides L.) for the treatment of bovine colic using the developed technology. The composition of the ingredients per 100 g of ointment consists of the following components: medical petroleum jelly – 70 g, anhydrous lanolin - 20 g, chamomile extracts and aloe juice – 5 g each. For sea buckthorn oil, 1 kg of ripe berries and 0.5 liters of vegetable oil were taken. The quantitative content of lactoferrin (LF) and secretory immunoglobulin A (sIgA) in the lacrimal fluid of the eye was determined by ELISA, the amount of lysozyme was determined by turbidimetric method by the rate of lysis of Micrococcus lysodeikticus suspension. Scientific studies were conducted on 20 animals of the Holstein-Frisian cattle breed infected with ICK, which were divided into experimental and control groups of 5 animals each. The obtained research results showed that the quantitative indices of LF, secretory lysozyme and sIgA are significantly lower than the physiological norm. It was found that under the influence of phytomases, the levels of the studied indicators significantly increase compared with the control group of animals. It was revealed that the most pronounced effect is provided by the use of a combined scheme of application of prepared phytopreparations. Studies have shown that the maximum increase in LF levels compared to the control group was up to 10.1 – 28.6%, secretory lysozyme-up to 16.1 - 37.2%, and sIgA-1.5 - 2 times higher. Based on the results of the study, the authors further recommend manufactured phytomases for the treatment of bovine colic, since phytopreparations are environmentally friendly, economically beneficial natural products with a high pharmacotherapeutic effect.